O przynależności kulturowej materiałów z osady na stanowisku 1 w Biskupicach, pow. sieradzki, woj. łódzkie - Muzolf, Przemysław (Acta Universitatis Lodziensis. Folia Archaeologica, 2019)
The settlement in Biskupice is located on the left bank of the Warta river, about 7 km north of Sieradz. It is a headland elevated about 10 m above the valley floor, and limited to the west and north by a drainage valley (Fig. 1). The first excavations in Biskupice were carried out in 1954 in the area of two small trenches. There was recorded a blackening of soil of considerable size, now defined as feature 1 (Fig. 2, 3). No subsequent materials were obtained until 2010, when a storage pit with a pear-shaped profile was discovered – feature 2. During the field studies, a total of 374 fragments of ceramic vessels and 655 animal bones were acquired. The collection from Biskupice included vessels decorated with the use of a single, all-round plastic strip (Fig. 4: 1–3, 6, 8, 9; 5: 2, 4; 6: 3–6; 8: 1, 3, 4) as well as a double one (Fig. 6: 5; 8: 4); a single strip decorated with finger impressions was also recorded. Two types of knobs were discovered: 1 – oval/round (Fig. 7: 2, 8), and longitudinal (Fig. 4: 4; 5: 1; 6: 7; 7: 7). The finds characterised by the imprint technique included the “textile ornament” combined with the motif of a single all-round strip with finger impressions. Vessels with rims of A type – non-thickened prevail, thickened rims (type B) and thinned (type C) were sporadically noted. The main form of containers in Biskupice were pots of G111 variant with two types: G111a with almost cylindrical rim (Fig. 4: 3, 9; 5: 2; 6: 5; 8: 2) and G111b with rim turned outside (Fig. 4: 1, 2, 6, 8; 5: 1, 4; 6: 4; 8: 1). Their ornamentation includes single, as well as double smooth all-round strip with finger impressions and knobs. Other finds included vases with conical necks/rims, decorated with knobs (Fig. 4: 4; 5: 7; 6: 10) and an amphora (Fig. 6: 1). The list of forms is complemented with mugs and bowls in the hemispherical variation M1 (Fig. 5: 5, 6; 6: 2; 7: 7) and profiled M3 (Fig. 7: 1). There were distinguished two stylistic groups. One was assigned to the Trzciniec culture and it was represented by complexes of HT3–HT4 type in Kuyavia. The other group contained vessels decorated with a textile ornament, as well as a single strip decorated with fingernail impressions. Due to the tectonics, these vessels were included to the Mad’arovce- Věteřov-Únětice circle (generally, the Older Únětice circle). On the basis of the existing elements among the ceramic forms, the duration of the settlement in Biskupice falls between the end BrA2 and the 1st half of BrB2, which is dated to 1750–1450 BC. However, taking into account the result of 14C, the duration of the settlement in Biskupice should be located in the years 1750–1600 BC and it should be clearly attributed to the population of the Trzciniec culture, in whose vicinity the materials originating from the Older Únětice circle were recorded. Moreover, which is perhaps the most important matter, the coexistence of materials with such a different cultural provenance suggests a possibility of the existence of a syncretic cultural Trzciniec-Older Únětice group in Biskupice (or in its region).